Total alkaloids from Coptis chinensis Franch ameliorate hyperlipidemia and hepatic steatosis via dual pathway modulation of AMPK/SREBP-1c and PPARα/LXRα in mice - Li, Xiangyang; Zhang, Xiaomin; Wei, Nina; Peng, Haibo; Niu, Xianli (Frontiers in Pharmacology, 2025)
IntroductionHyperlipidemia and its associated hepatic steatosis pose significant global health burdens, necessitating novel therapeutic strategies. Coptis chinensis Franch total alkaloids (TAC) exhibit lipid-modulating properties, but their mechanistic underpinnings remain incompletely elucidated. We aim to evaluate the therapeutic efficacy and molecular mechanisms of TAC in a murine model of hyperlipidemia-associated NAFLD.Materials and methodsHigh-fat diet (HFD)-fed C57BL/6 mice received TAC (2.5, 5.0, 10.0 g/L) or simvastatin for 2 weeks. Metabolic parameters, serum lipid profiles, hepatic function markers, and histopathology were systematically analyzed. Molecular pathways were interrogated through qPCR, Western blot, and pharmacological inhibition of AMPK (Compound C) and PPARα (GW6471).ResultsTAC treatment demonstrated significant dose-dependent improvements across multiple parameters. Compared to HFD controls, TAC reduced body weight by 21.3% and liver index by 18.7%, while lowering fasting blood glucose levels by 32.4%. Serum analyses showed substantial reductions in total cholesterol (46.2%), triglycerides (38.5%), and LDL-cholesterol (52.1%), accompanied by a 29.8% increase in HDL-cholesterol. Hepatic function improved markedly, with ALT and AST levels decreasing by 57.3% and 49.6% respectively. Histopathological examination revealed a 68.4% reduction in hepatic lipid accumulation. At the molecular level, TAC treatment resulted in a 2.7-fold increase in AMPK phosphorylation while significantly reducing HMGCR expression by 63.1% and nuclear SREBP-1c levels by 71.5%. Concurrently, TAC upregulated PPARα and LXRα expression by 3.1-fold and 2.4-fold respectively, leading to enhanced expression of lipolytic enzymes LPL and HL by 2.8-fold and 2.1-fold. These beneficial effects were completely abolished by co-treatment with pathway-specific inhibitors.ConclusionTAC ameliorates hyperlipidemia and hepatic steatosis through dual modulation of AMPK/SREBP-1c-mediated lipid synthesis and PPARα/LXRα-driven lipolysis, presenting a multifaceted therapeutic approach for metabolic disorders.